2016
DOI: 10.1049/htl.2016.0061
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of rollator use using inertial sensors

Abstract: The use of walking aids is prevalent among older people and people with mobility impairment. Rollators are designed to support outdoor mobility and require the user to negotiate curbs and slopes in the urban environment. Despite the prevalence of rollators, analysis of their use outside of controlled environments has received relatively little attention. This Letter reports on an initial study to characterise rollator movement. An inertial measurement unit (IMU) was used to measure the motion of the rollator a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 16 publications
0
13
1
Order By: Relevance
“…The results reveal the necessity of not only studying gait in laboratory conditions, but especially in everyday conditions. For this purpose, Cheng et al [32] suggested the use of wearable inertial sensors to determine the interaction between the rollator, the user and the walking environment.…”
Section: Discussionmentioning
confidence: 99%
“…The results reveal the necessity of not only studying gait in laboratory conditions, but especially in everyday conditions. For this purpose, Cheng et al [32] suggested the use of wearable inertial sensors to determine the interaction between the rollator, the user and the walking environment.…”
Section: Discussionmentioning
confidence: 99%
“…It is worthwhile to compare the findings in this paper with our previous research [14]. In our earlier work we collected data over a number of periods of straight line walking over different surfaces.…”
Section: Discussionmentioning
confidence: 81%
“…Due to the nature of the preceding calculations, and the propensity for accelerometer data to drift, the velocity estimate must be rebased, in accordance with the authors previous work [14]. This is achieved by estimating the baseline by interpolating through the points when the velocity estimate is considered to show no movement, referred to as zero points.…”
Section: E: Speed and Distance Calculationmentioning
confidence: 99%
See 2 more Smart Citations